2015
DOI: 10.1002/adma.201503342
|View full text |Cite
|
Sign up to set email alerts
|

All Chemical Vapor Deposition Synthesis and Intrinsic Bandgap Observation of MoS2/Graphene Heterostructures

Abstract: A facile all-chemical vapor deposition approach is designed, which allows both sequentially grown Gr and monolayer MoS2 in the same growth process, thus allowing the direct construction of MoS2 /Gr vertical heterostructures on Au foils. A weak n-doping effect and an intrinsic bandgap of MoS2 are obtained from MoS2 /Gr/Au via scanning tunneling microscopy and spectroscopy characterization. The exciton binding energy is accurately deduced by combining photoluminescence measurements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
124
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 138 publications
(144 citation statements)
references
References 47 publications
(55 reference statements)
18
124
0
2
Order By: Relevance
“…4(a); orange crosses) [23,42,[47][48][49] are within 100 meV of our estimated value. We also note that the band gap we measured at the residual doping condition is comparable to recent photocurrent [50] and PLE [29,30] measurements, but substantially higher than scanning tunneling microscopy (STM) measurements of ML-MoS2 on conductive substrates [22,51]. And further, a recent STM study of suspended ML-MoS2 [52] finds a gap approaching the value we determined for the zero-doping condition.…”
Section: Resultssupporting
confidence: 88%
“…4(a); orange crosses) [23,42,[47][48][49] are within 100 meV of our estimated value. We also note that the band gap we measured at the residual doping condition is comparable to recent photocurrent [50] and PLE [29,30] measurements, but substantially higher than scanning tunneling microscopy (STM) measurements of ML-MoS2 on conductive substrates [22,51]. And further, a recent STM study of suspended ML-MoS2 [52] finds a gap approaching the value we determined for the zero-doping condition.…”
Section: Resultssupporting
confidence: 88%
“…Such a discrete six-fold FT pattern would suggest a dominant orientation of the crystallized MoS 2 that in turn opens the interesting question whether this dominant orientation may be related to a possible epitaxial relationship of the MoS 2 to the underlying graphene support. Previous literature suggested that the nonexistence 22,69,70 or existence 22,71,72 of MoS 2 /graphene epitaxy is highly process parameter dependent, resulting from the rather weak van der Waals interaction between MoS 2 and graphene. 69 When MoS 2 /graphene epitaxy was found in previous work, rotational misalignment distributions peaked at 0° and 30°.…”
Section: Resultsmentioning
confidence: 99%
“…The material of La 22 AC Impedance Spectroscopy measurements of the ceramics were performed with a Solatron 1260 Impedance/Gain-Phase Analyzer over a frequency range of 0.1-10 7 Hz from room temperature to 700 °C in air. Prior to the measurements, gold were pasted on both sides of the ceramic pellets and then heated at 550 °C for 40 min in air in order to get the electrodes.…”
Section: Methodsmentioning
confidence: 99%